2023
DOI: 10.2147/jmdh.s393061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Tools for Pulmonary Involvement in Patients with Ankylosing Spondylitis: Is Diaphragmatic Ultrasonography Correlated to Spirometry?

Abstract: Objective Spondyloarthritis (SpA) is a chronic inflammatory rheumatic disease that can lead to spinal ankylosis and consequently, restrictive pulmonary dysfunction. Thus, the present study aimed to assess the accuracy of diaphragm ultrasound compared to spirometry in the screening of restrictive pulmonary disorders in radiographic SpA patients. Methods We conducted a cross-sectional study of 50 patients with radiographic SpA, over six months. Sociodemographic data, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…This was confirmed by the results of spirometry from the same study, which indicated restrictive disorders in 32% of the subjects and pathological values of chest motility in 72%. Diaphragmatic thickness was found to correlate with FVC and supine FVC, further confirming the correlation between ultrasound diaphragmatic assessment and spirometry results ( 66 ).…”
Section: Ultrasound Assessment Of Diaphragm Function and Its Signific...supporting
confidence: 66%
“…This was confirmed by the results of spirometry from the same study, which indicated restrictive disorders in 32% of the subjects and pathological values of chest motility in 72%. Diaphragmatic thickness was found to correlate with FVC and supine FVC, further confirming the correlation between ultrasound diaphragmatic assessment and spirometry results ( 66 ).…”
Section: Ultrasound Assessment Of Diaphragm Function and Its Signific...supporting
confidence: 66%